Glioblastomas require integrin αvβ3/PAK4 signaling to escape senescence - Franovic, Aleksandra (Cancer Res, 2015)
Integrin αvβ3 has been implicated as a driver of aggressive and metastatic disease, and is upregulated during glioblastoma progression. Here we demonstrate that integrin αvβ3 allows glioblastoma cells to counteract senescence through a novel tissue-specific effector mechanism involving recruitment and activation of the cytoskeletal regulatory kinase PAK4. Mechanistically, targeting either αvβ3 or PAK4 led to emergence of a p21-dependent, p53-independent cell senescence phenotype. Notably, glioblastoma cells did not exhibit a similar requirement for either other integrins or additional PAK family members. Moreover, αvβ3/PAK4 dependence was not found to be critical in epithelial cancers. Taken together, our findings established that glioblastomas are selectively addicted to this pathway as a strategy to evade oncogene-induced senescence, with implications that inhibiting the αvβ3/PAK4 signaling axis may offer novel therapeutic opportunities to target this aggressive cancer.